The Principal Strategies in Improving Teachers’ Professional Competence at Public Elementary School in South Aceh - Risawaton, Aja Syarifah; AR, Murniati; Khairuddin, Khairuddin (FKIP Universitas Lampung, 2020)
The Principal Strategies in Improving Teachers’ Professional Competence at Public Elementary School in South Aceh. Objectives: The purposes of this research are to understand the programs, strategies, and principals’ obstacles and supporting factor in inproving teachers’ professional competence at Public Elementary School in Aceh Selatan, Indonesia. Methods: This research uses descriptive method with qualitative approach. This research uses descriptive method with qualitative approach. Data collection were conducted through interviews, obsevation, and documentation studies. The subject of this research is the principals and teachers. Findings: The results of this research showed (1) preparation of the principal’s program in improving teacher professionalism such as: annual program, semester program, steps arragement of learning plan such as syllabus, lesson plan, and etc., (2) The Strategies in improving teachers’ professional include: Division of tasks, holding the training and attending the teachers working group. (3) the teachers have all mastered IT, most of teachers are undergraduate student, and most teachers have the teaching certificate.Keywords: Principal strategies, teachers’ competence, public elementary school.DOI: 10.23960/jpp.v10.i1.202007